Preliminary study: the use of sugarcane juice to replace white sugar in an effort to overcome diabetes mellitus. Issue 1 (April 2020) - Ayuningtyas, R A; Wijayanti, C; Hapsari, N R P; Sari, B F P; Subandi,
Abstract: The prevalence of diabetes mellitus, especially type 2 diabetes mellitus, continues to increase. One of the characteristic type 2 diabetes mellitus is insulin resistance, which caused by lack of trivalent chromium. This is occurred because the habits of the people, who consume white sugar more than brown sugar or sugarcane juice. Refining process will eliminate the mineral content in white sugar. Mineral content in white sugar is assumed to be lower than brown sugar or sugarcane juice. Consuming sugarcane juice as a substitute for white sugar is also thought to be able to increase the level of chromium in the body's cells. It will be publicly accepted in organoleptic. The purpose of this study are to compare the levels of chromium in sugar and sugarcane juice, to know level of chromium in the blood and urine of healthy and diabetes mellitus patients before and after consuming sugarcane juice and to know the level of consumers' preference to the flavour of white sugar compared to sugarcane juice. Samples of sugarcane juice and white sugar products were obtained from a sugar factory in Java. Determination of chromium content was carried out by dry destruction using Atomic Absorption Spectrophotometer. Organoleptic test was performed using a preference test of 30 untrained respondents. The results had shown that the chromium levels in sugarcane juice were 35 times higher than in white sugar has; sugarcane juice consumption for one month apparently can increase the levels of chromium (both in the blood and in the urine of people) but increased level in diabetes mellitus patients higher than healthy people; and in the terms of the taste, the average respondents' preferences for sugarcane juice and white sugar is the same. This preliminary study showed that sugarcane juice is potential to overcome diabetes mellitus type 2.